2016
DOI: 10.1007/s12011-016-0871-4
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fluorine on the Disturbances of Homeostasis in the Central Nervous System

Abstract: Fluorides occur naturally in the environment, the daily exposure of human organism to fluorine mainly depends on the intake of this element with drinking water and it is connected with the geographical region. In some countries, we can observe the endemic fluorosis—the damage of hard and soft tissues caused by the excessive intake of fluorine. Recent studies showed that fluorine is toxic to the central nervous system (CNS). There are several known mechanisms which lead to structural brain damage caused by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(67 citation statements)
references
References 102 publications
2
51
1
2
Order By: Relevance
“…These results may be explained by delay in the neuro-maturation of the monoaminergic systems and/or imbalance between the synthesis and degradation of these monoamines (El-Habibi, Mousa, & Mohamed, 2011;Pereira, Dombrowski, Losso, Chioca, Da Cunha, & Andreatini, 2011). It has been shown that exposure to aluminum/sodium fluoride during the gestational and lactational periods induced persistent neurobehavioral deficits in the offspring due to the ability of aluminum and fluoride to transport through the placental barrier and to cross the blood-brain barrier (Dec et al, 2017;Panchal & Verma, 2014;World Health Organization, 1996). Moreover, fluorine was found to induce deregulation in the secretion of serotonin, dopamine, norepinephrine, acetylcholine, and epinephrine in the hippocampus, striatum, and cerebral cortex (Dec et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may be explained by delay in the neuro-maturation of the monoaminergic systems and/or imbalance between the synthesis and degradation of these monoamines (El-Habibi, Mousa, & Mohamed, 2011;Pereira, Dombrowski, Losso, Chioca, Da Cunha, & Andreatini, 2011). It has been shown that exposure to aluminum/sodium fluoride during the gestational and lactational periods induced persistent neurobehavioral deficits in the offspring due to the ability of aluminum and fluoride to transport through the placental barrier and to cross the blood-brain barrier (Dec et al, 2017;Panchal & Verma, 2014;World Health Organization, 1996). Moreover, fluorine was found to induce deregulation in the secretion of serotonin, dopamine, norepinephrine, acetylcholine, and epinephrine in the hippocampus, striatum, and cerebral cortex (Dec et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that exposure to aluminum/sodium fluoride during the gestational and lactational periods induced persistent neurobehavioral deficits in the offspring due to the ability of aluminum and fluoride to transport through the placental barrier and to cross the blood-brain barrier (Dec et al, 2017;Panchal & Verma, 2014;World Health Organization, 1996). Moreover, fluorine was found to induce deregulation in the secretion of serotonin, dopamine, norepinephrine, acetylcholine, and epinephrine in the hippocampus, striatum, and cerebral cortex (Dec et al, 2017). In this regard, it was reported that the potential implications of aluminum in the etiopathogenesis of neurological disorders were attributed, at least in part, to its inhibitory effect on the activity of dopamine-beta-hydroxylase (Milanese, Lkhayat, & Zatta, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have focused on fluorine neurotoxicity. The central nervous system during development is highly sensitive to the influence of fluorine due to its weakened protective mechanisms [66]. Studies showed that children in high fluoride areas had significantly lower IQ (intelligence quotient) scores than those who lived in low fluoride areas [67,68].…”
Section: Nervous System Toxicitymentioning
confidence: 99%
“…Fluorine causes glial cell activation which is involved in inflammation through producing proinflammatory cytokines. Chronic inflammation in the brain appears to cause neuronal damage [66,75]. Moreover, fluorine influences the synthesis of neurotransmitters, the activity of enzymes, the expression of receptors, and the plasticity of neurons [76][77][78].…”
Section: Nervous System Toxicitymentioning
confidence: 99%
See 1 more Smart Citation